Effects of propofol on the cognition and hippocampal N-methyl-D-aspartate subunits expression in an MPTP-induced Parkinson’s disease rat model - Zhu, Ping; Zhang, Yongyan; Xu, Hua; Ren, Yu (Frontiers in Behavioral Neuroscience, 2025)
IntroductionParkinson’s disease (PD) is associated with higher risk of cognitive impairment. Until now, little is known about the effect of anesthetics on cognitive function in PD patients. The imbalance of hippocampal N-methyl-D-aspartate (NMDA) receptors NR2A/NR2B subunit ratio is reported to be associated with memory dysfunction in PD rats. The current study investigated the effects of propofol on the cognitive function and hippocampal NR2A/NR2B ratio in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD rat model.MethodsMPTP was stereotaxically injected into the substantia nigra pars compacta of male Wistar rats. Next day (day 2), the rats in the chronic intervention groups were injected daily with either propofol (80 mg/kg/day, i.p.) or fat emulsion for 7 days (day 2–8). The rats in the acute intervention groups received propofol or fat emulsion only on day 8. Then, all the rats underwent an open field test and an inhibitory avoidance (IA) test. At last, the rats were killed for histological analysis and hippocampal NR2A and NR2B proteins and mRNA level quantification.ResultsNeither acute nor chronic treatment with propofol can significantly change the impairment of locomotor activity and dopaminergic denervation of the striatum in MPTP-lesioned rats. MPTP lesioning caused IA memory impairment, which was aggravated by chronic treatment with propofol. Furthermore, chronic treatment with propofol also aggravated the imbalance of hippocampal NR2A/NR2B ratio in MPTP-lesioned rats.DiscussionThe current findings indicate that chronic propofol treatment exacerbated MPTP-induced inhibitory avoidance (IA) memory impairment and aggravated the imbalance of hippocampal NR2A/NR2B ratio in MPTP-lesioned rats. Our current data demonstrate a correlation, not direct causation, between NR2A/NR2B dysregulation and cognitive impairment. Future studies should probe whether this imbalance is a driver or consequence of synaptic dysfunction.